Tenascin-C provokes cardiac fibrosis and endothelial impairment in Duchenne Muscular Dystrophy. (10th June 2022) - Szabo, P L; Inci, M; Hilber, K; Abraham, D; Trojanek, S; Costantino, S; Paneni, F; Podesser, B K; Kiss, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWF Austrian Science Fund Cardiac fibrosis and dilated cardiomyopathy are major contributors to mortality in Duchenne muscular dystrophy (DMD) patients. There is a growing collection of evidence that Tenascin C (TN-C) plays a maladaptive role in cardiac remodelling and fibrosis. Our aims were to 1) assess the vascular dysfunction and cardiac fibrosis and its link to TN-C in a mouse model of DMD and 2) explore the effect of knocking out TN-C in dystrophic mice. Male wt, mdx and mdx TN-C KO age-matched mice were used. Cardiac fibrosis was assessed on tissue sections. Wire myography was used to test the vascular reactivity and endothelial cells (ECs) were isolated from mouse lung tissues to characterize the oxidative stress and inflammatory marker expression. To study the signalling pathways contributing to cardiac fibrosis, human cardiac fibroblasts (hCFs) were treated with TN-C or TGF-β and gene expression and epigenetic regulation of p65 were assessed. Cardiac fibrosis was markedly increased in mdx mice which was accompanied with elevated TN-C level in cardiac tissue and plasma compared to wt animals. In addition, endothelial cells isolated from mdx mice also showed a marked upregulation of oxidative stress and inflammatory markers and in line with that vascular endothelial function was impaired in mdx mice. Interestingly, mdx- TN-C KO mice showed preserved vascular function as well as reduced cardiac fibrosis compared to age-matched mdx mice. hCFs treated with TN-C or TGF-β showed increased collagen and α-SMA expressions which could be reduced by TN-C siRNA. In addition, both TN-C and TGF-β promote p65/NF-κB promoter demethylation and subsequently stimulate pro-inflammatory and pro-fibrotic signalling, which could be reversed by applying p38 MAPK inhibitor in hCFs. TN-C promotes oxidative stress and inflammation in ECs and fibroblasts, contributing to severe endothelial dysfunction and cardiac fibrosis. In addition, activation of NF-κB p65 signalling pathway may play a role in TN-C induced fibrosis. Thus, TN-C may be a critical mediator and potential target for therapy in DMD.